The Relationship Between Mental Workload and Sleep Quantity with Work Fatigue among Haul Dump Truck Operators in Coal Mining - Asti Puspita Nurahma; Indriati Paskarini; Endang Dwiyanti; Sahabat Sutanto (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: In mining production activities, haul dump trucks are utilized for transportation purposes and are driven by an operator. The haul dump truck operator works in a shift work system consisting of 12 working hours. The workers are required to always control the steering speed, causing potential work fatigue. This study aimed to analyze the relationship between mental workload and sleep quantity with work fatigue among haul dump truck operators. Method: This study was a quantitative research study using a cross-sectional design. The population was 179 haul dump trucks operators, while the sample was 123 respondents determined through simple random sampling. The variables of this study were age, years of service, education level, mental workload, sleep quantity, and work fatigue complaints. The data was tested using the Chi-Square test. The instruments used to obtain the data were the National Aeronautics and Space Administration Task Load Index and the Work Fatigue Measurement Tool Questionnaire. Result: The haul dump truck operators (54.5%) had a high mental workload, low sleep quantity (61.8%) with less than 7 hours of sleep, and moderate fatigue complaints (44.7%). There was a significant relationship found between age (P-value = 0.018), years of service (P-value = 0.039), and sleep quantity (P-value = 0.001) with work fatigue complaints. The level of education and mental workload had a significance value above 0.05. Conclusion: Sleep quantity has a significant relationship with work fatigue complaints. This can be responded to by intensifying the information on the socialization of fatigue and the importance of maintaining the quality of sleep.